Improved method for determining an alternative set of numbers in a system of residual classes - Краснобаев, В.А.; Кошман, С.А.; Янко, А.С. (Radiotekhnika, 2017)
The most well-known practical methods for alternative set (AS) determining of numbers in the residue number system (RNS) are analyzed. The main disadvantage of the considered methods consists in a considerable time of the AS determining. To reduce the time of the AS determining in the RNS the known method was improved. The essence of the improvement of the proposed method consists in the decrease of time needed for determining the AS numbers in the RNS.